Simulation of phosphorus movement in unconfined aquifer by means of visual MODFLOW. - Saghravani, Seyed Reza; Mustapha, Sa'ari; Ibrahim, Shaharin; Mohd. Zawawi, Mohd. Azwan; Randjbaran, Elias (Science Publications, 2010)
Problem statement: In three recent decays, computer software's are used for assessing and predicting of what happened and what will happen for surface and subsurface water. These supplementary tools are calculating and presenting potential recharge of contamination to estimate and assess important issue in hydrogeology such as amount of contamination in drinking water. There is a source of contamination in study area that was approved by some experiments in laboratory. In present study, movement of contamination horizontally and vertically simulated. Approach: Visual MODFLOW used to determine movement of groundwater and fate of contamination (phosphorus) by two different types of computers. Results: The results showed that both computers were able to run the software without critical problem. Also it was found that vertical migration is mainly responsible to migration of contamination. Conclusion: In conclusion, the software performance can be skilful and accomplished. It is able to solve a wide range of research problems with low rate of the errors.